Recommendations to mitigate against human health risks incurred due to energetic particle irradiation beyond low earth orbit/BLEO. (April 2015) - McKenna-Lawlor, Susan; Bhardwaj, Anil; Ferrari, Franco; Kuznetsov, Nikolay; Lal, Ajay K.; Li, Yinghui; Nagamatsu, Aiko; Nymmik, Rikho; Panasyuk, Michael; Petrov, Vladislav; Reitz, Günther; Pinsky, Lawrence; et al.
Abstract: An account is provided of the main sources of energetic particle radiation in interplanetary space (Galactic Cosmic Radiation and Solar Energetic Particles) and career dose limits presently utilized by NASA to mitigate against the cancer and non-cancer effects potentially incurred by astronauts due to irradiation by these components are presented. Certain gaps in knowledge that presently militate against mounting viable human exploration in deep space due to the inherent health risks are identified and recommendations made as to how these gaps might be closed within a framework of global international cooperation. Highlights: Health risks posed to astronauts during long duration space missions are significant. Gaps in scientific and technical information hamper mounting mitigating strategies. These gaps can be closed 'through making, recommended, coordinated, global studies. Risk management presents the best option today for improving human safety in space.